A review study on the effect of glass envelope, working fluid and geometry contributions for the receiver on performance of parabolic trough collector (PTC) - Abbas, Mohammed Saad; Sapit, Azwan; Balla, Hyder Hassan Abd; Haider, Ali Mohammed; Al-Shamani, Ali Najah (Asian Research Publishing Network (ARPN), 2018)
Renewable energy resources play an essential role in the sustainable energy development as they are friendly energy resources. Solar energy is one of the renewable energy sources are used in many fields from domestic/industrial fluid heating, cooking and electricity production. The parabolic trough collector (PTC) is adopted to be the good choice for medium temperature (150-400 °C) heat necessities. The admiration of solar PTC has generated utility in maximum efficiency energy potential. The heat transfer element (HTE) receiver portion of PTC is the main part in PTC assembly manufactured as tubular shape either without glass envelope or covered with a glass envelope to reduce the radiative and convective heat losses. This article focused on the main parameters was considered in the HTE receiver design of parabolic trough solar collectors (PTC) which were enhanced the heat transfer process in deep details. Further, this work extended to discuss the primary results that came from a different design of PTC receiver based on previous studies in order to benefits researchers who are interested in solar energy collectors. © 2006-2018 Asian Research Publishing Network (ARPN).